Broadband planar nearfield acoustic holography based on one-third-octave band analysis. (August 2016) - Zhou, Hefeng; Lopez-Arteaga, Ines; Nijmeijer, Henk
Abstract: Planar nearfield acoustic holography (PNAH) is usually based on narrow-band, single frequency analysis, which is time consuming when the source behavior over a broad frequency range is of interest, as is the case with many industrial sources. In this paper a method, broadband planar nearfield acoustic holography based on one-third-octave band analysis (BPNAH), is described. Data relating to the complex band pressure on the hologram is obtained by combining the root-mean-square pressure corresponding to a one-third-octave band with the phase of the pressure corresponding to a single frequency line. Numerical simulations and measurements show that the BPNAH method allows a significant reduction in processing time, while keeping a similar accuracy to the conventional reconstruction, which is based on the summation of frequency by frequency in the corresponding band. As a simple, time-saving and robust technique, the BPNAH method is particularly well adapted to industrial studies.